Intrusive Thoughts Elicited by Direct Electrical Stimulation during Stereo-Electroencephalography - Popa, Irina; Donos, Cristian; Barborica, Andrei; Opris, Ioan; Mălîia, Mihai Dragoş; Ene, Mirela; Ciurea, Jean; Mîndruţă, Ioana (Frontiers in Neurology, 2016)
Cortical direct electrical stimulation (DES) is a method of brain mapping used during invasive presurgical evaluation of patients with intractable epilepsy. Intellectual auras like intrusive thoughts, also known as forced thinking (FT), have been reported during frontal seizures. However there are few reports on FT obtained during DES in frontal cortex. We report three cases in which we obtained intrusive thoughts while stimulating the dorsolateral prefrontal cortex and the white matter in the prefrontal region. In order to highlight the effective connectivity that might explain this clinical response, we have analyzed cortico-cortical potentials evoked by single pulse electrical stimulation.